Co-worker Relations and Working Environment: Influences on Turnover Intentions in Co-operatives of Surkhet - Sharma Gaire, Amrit Kumar (Interdisciplinary Journal of Innovation in Nepalese Academia, 2023)
This study aims to construct a conceptual framework for analyzing and forecasting the factors that influence employee turnover intentions in cooperative organizations in Surkhet, Nepal. Cooperatives play a crucial role in economic growth as they generate jobs, collect and invest funds, and offer a wide range of public services. Cooperatives engage in various activities to achieve their objectives, but they have been struggling with high turnover rates. The study employed a cross-sectional design, with data collected in a single contact with the respondents. The study's demographic consisted of all cooperative employees in Surkhet, and a convenience sampling method was used to gather 167 responses through a structured Likert questionnaire. Data analysis was conducted using SPSS and AMOS 23 software, with structural equation modeling as the statistical tool for hypothesis testing. Hypotheses were formulated using a deductive research approach. The results indicate that co-worker relations and the working environment were significantly associated with employee turnover intentions among cooperative employees. However, promotions showed no significant association with turnover intentions. This study has certain limitations, including the use of cross-sectional data, self-reports, variations in employee education levels, the comprehension of content, and a relatively small sample size. The respondents were a relatively uniform group of employees, so the results may not be generalized to other employees and institutions. Nevertheless, the study's findings suggest that cooperative organizations should place greater emphasis on improving co-worker relations and the working environment to reduce turnover intentions. This research can be particularly useful for managers in cooperative organizations.